Privatization in developing countries : Latin America experience Chile, Mexico and suggestions for Ecuador - Barreiros Armendariz, Rubén Dario ([Antwerpen]: Universiteit Antwerpen)
"Barreiros Armendariz, Rubén Dario Master's Dissertation in Public Administration and Management, Universiteit Antwerpen"